Financial Feasibility Of Waste To Food Business Model As Integrated Alternative Solution To Solve Waste Problem & Food Security (The Indonesian Journal of Business Administration, 2020)
This research examines the feasibility of Waste to Food concept program from the financial side and determines alternatives in its implementation. Waste to Food is a solution idea in handling organic waste while supporting the food security program. In the concept of this program, the people involved will be invited to separate organic waste and store it in the Black Soldier Fly maggot reactor (the product of LPIK ITB innovation). In the reactor, organic waste will be processed by maggot Black Soldier Fly (BSF) and later the maggot BSF will become a source of animal feed. In this study, selected livestock were laying hens. So, the final food product of this program is eggs. The calculation in this study was carried out within the scope of the RW scale involving 200 houses, 200 laying hens and the calculation time for 5 years.Before creating the business model and making a feasibility calculation, analysis is done first through the PESTLE & SWOT analysis method, literature studies, interviews & group discussion forums with experts and relevant stakeholders are also carried out in this study in determining considerations, assumptions and alternatives choices which are then examined. There are 4 variables that become criteria in alternative scenarios, the composition of laying hens feed from maggot BSF, eggs production, eggs prices and labour wages. For the composition of feed from maggot, this study made 3 alternatives that are 80%, 50% and 20%. For eggs production, the alternatives that chosen are 90%, 80% and 70%. For the price of eggs, the alternatives are Rp. 26.000, Rp. 23.000, and Rp. 20.000. For the labour wages, the alternatives are Rp 3.500.000, Rp 2.800.000, Rp 2.100.000.The optimistic scenario calculation shows the results of the Internal Rate Return (IRR) of 38,1 % and the Payback Period (PP) of 3 years. Calculations for moderate scenarios show IRR results of 23,62 % and PP 3 years 7 months. Calculations for the pessimistic scenario show an IRR of 18,97 % and a PP of 3 years 9 months. After calculating the financial feasibility study, the results show that the Waste to Food program is financially feasible for all scenarios and can be an alternative model that can be applied. Besides factors related to finance & business; collaboration with citizens and all stakeholders, determination of rewards for those involved, has become an important support in the successful implementation of Waste to Food. Keywords: organic waste, Black Soldier Fly Larvae, Maggot BSF, waste to food, food security, laying hens, eggs